Analisis Persepsi Masyarakat dan Peran Lingkungan Sosial Terhadap Minat Menabung di Bank Syariah - Feby Efriani; Tri Fitri Juliani; Lidia Desiana (Jurnal Semesta Ilmu Manajemen dan Ekonomi, 2024)
This study aims to analyze the impact of public perception and social environment on the interest in saving at Islamic banks, specifically within the Jakabaring Central Market community in Palembang. Perceptions influenced by religious beliefs, as well as social support from family, friends, and workplaces, play a crucial role in shaping individuals' decisions to use Islamic banking products. With a social environment that supports Sharia principles, Islamic banks hold significant potential to enhance public trust and interest, especially in religious market communities.